The Rhythm of Many: Biological Rhythms in the Marine Environment, From Macro-Scale Planktonic Ecosystems to Micro-Scale Holobionts - Hewitt, Olivia H.; Shaikh, Hisham M. (Frontiers in Marine Science, 2021)
Daily environmental oscillations that follow Earth’s rotation around the Sun set a metronome for life, under which all organisms have evolved. Entrainment to these cues allow organisms to rhythmically set the pace of their own endogenous biological clocks with which the timings of diverse cellular activities are coordinated. In recent years, our knowledge of biological rhythms has extended across all domains of life. This includes both free-living and symbiotic life forms. With the insurgence of metagenomic sequencing tools, the field of holobiont chronobiomics (encompassing chronobiology of host and its associated microbiota) has recently opened and gained significant traction. Here, we review current knowledge regarding free-living prokaryote rhythmic regulation before exploring active areas of research that consider the coordinated rhythmic regulatory activities of hosts and their symbionts as a single entity, i.e., holobiont, and even the extent to which rhythmicity influences virus–host interactions. We describe rhythmicity within non-photosynthetic bacteria, cyanobacteria, and archaea, before investigating the effect of light, and, thus, diel cycle, on viral life cycles and host–virus population dynamics in marine planktonic ecosystems along with their potential to influence host cyanobacterial circadian clocks. We then explore current evidence outlining coordinated rhythmic regulation within marine holobionts and the significance of this for holobiont health and adaptive fitness that, in turn, optimizes their success within their local environments. Finally, we assess the critical role of circadian regulation for holobiont innate immunity and metabolism within well-studied non-marine mammalian systems, and, thus, assess how this can guide us within understudied marine chronobiomics research.